Quantitative Assessment of the Reinforcement Distribution Homogeneity in CNT/Metal Composites1. Issue 7 (23rd December 2014) - Rossi, Paulo; Suarez, Sebastian; Soldera, Flavio; Mücklich, Frank
<x xml:space="preserve">Abstract</x> Reinforcement distribution has a major influence on composite material behavior. This work presents a method to quantitatively analyze the reinforcement distribution homogeneity in metal matrix composites reinforced with carbon nanotubes. The method is based on the statistical two‐dimensional analysis of the CNT cluster distribution within defined regions. A subsequent analysis of the material hardness allowed a correlation to the homogeneity, highlighting the influence of the CNT distribution. This analysis provides a straightforward and objective assessment of the reinforcement distribution, applicable to other types of composites.